(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Background: Growth hormone is used to treat short stature and growth failure associated with growth disorders. Growth parameters at birth and growth hormone status variably modulate response to growth hormone therapy. Aim of the study: To compare growth response between short small for gestational age and growth hormone deficient children during the first year of growth hormone treatment and to see the differences between them at presentation regarding age and sex. Patients and methods: Randomized controlled trials were done at the Endocrine and Diabetic Center in the Central Teaching Hospital of Pediatric in Baghdad City within the period started from Nov. 1, 2021, to the end of Nov. 2022. The study population was 100 short prepubertal children aged between 3–13 years, 50 patients diagnosed with growth hormone deficiency (GHD) and 50 with small for gestational age (SGA), and both were arranged for growth hormone (GH) treatment; GHD group was classified according to growth hormone level in the provocation test into severe GHD (max GH <3 ng/ml), and mild GHD (max GH 3-7 ng/ml). Both groups (GHD and SGA) were classified according to the average GH dose used during the first-year treatment into: [in GHD group low dose <= 0.03 (μg/kg. Day) and high dose > 0.03 (μg/kg. Day) and in SGA group into low dose <= 0.045 and high dose >0.045 (μg/kg. Day)] and see the growth response after six months and one year of treatment. Main Outcome Measure: For each patient group, growth response parameters (height velocity and change in height standard deviation) during the first six months and one year of GH treatment were established. Results: Responses to GH in terms of change in height standard deviation (ΔHt SDS) after one-year treatment were greatest in both groups (GHD and SGA) in age group =<5 years with p=0.0001, p=0.0001 respectively. Also, the height velocity (HV) was significantly better in the same age group in GHD patients with p=0.005. In the SGA group, there was greatest response with high dose GH (>0.045 µg/kg/day) in terms of HV and ΔHt SDS with (p=0.0001 and p=0.006 respectively). Moreover, the response after one year of treatment in both groups were good response (ΔHt SDS >0.3), even in the SGA group but with a high dose of growth hormone. Also, as a comparison in HV between the two groups (GHD vs. SGA), the greatest response was in the GHD group with a significant P-value (p=0.002). Conclusion: Younger age at diagnosis and treatment with growth hormone are associated with better response in ΔHt SDS and growth velocity for both small for gestational age and growth hormone deficient patients. High dose of growth hormone (>0.045µg/kg/day) is associated with better response in ΔHt SDS and growth velocity in the first-year treatment in SGA patients. In a comparison in response after one year of treatment with growth hormone between GHD and SGA children, the response to GH treatment was significantly better in the GHD group than in the SGA group in ΔHt SDS and growth velocity; moreover, both of them had a good response to GH after first-year treatment (ΔHt SDS >0.3).